Memorial to Richard Cobbe - Ghosh, Ayan (2023)
Memorial to Richard Cobbe, the East India Company chaplain who "stirred up his countrymen to complete the church." Though the foundation stone was laid in 1676, construction got delayed due to a lack of funds, raids by hostile enemies, and repeated plague outbreaks. The church was consecrated for divine worship on Christmas Day, 1718.